ANALISIS PERAN DAN KONTRIBUSI UMKM DALAM MENINGKATKAN PDRB DAN PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA SELATAN - Risah Risah; Cia Lesta Ega; Gustina Masitoh (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the role of Micro, Small, and Medium Enterprises (MSMEs) in increasing Gross Regional Domestic Product (GRDP) and economic growth in South Sumatra Province. The method used in this research is a descriptive quantitative approach utilizing secondary time series data from 2022 to 2024 obtained from the Central Bureau of Statistics (BPS) of South Sumatra Province, supported by a literature review. Data analysis techniques include trend analysis, data classification, and interpretation of the contribution of MSME-dominated sectors to Gross Regional Domestic Product (GRDP). The results show that sectors dominated by MSMEs, such as accommodation and food service activities, manufacturing, and information and communication, have a significant contribution to regional economic growth. The accommodation and food service sector is the highest contributor despite experiencing a declining trend over the years, while the information and communication sector shows a significant increase in 2024. Overall, economic growth in South Sumatra has fluctuated but continues to show a positive trend with recovery in several key sectors. Thus, MSMEs are proven to play a strategic role in driving regional economic growth through job creation, increasing community income, and strengthening the local economic structure.